Effect of antiprogestin RU 486 on the proliferation and metabolic activity of stromal cells separated from human endometrium - Bhargava-Periwal, S.; Farooq, A.; Bhargava, V.L.; Bhatla, N.; Vij, U.; Murugesan, K. (Contraception (Stoneham), 1996)
The effects of RU 486 on the proliferation and metabolic activity of human endometrial stromal cells in culture were studied. RU 486 at 10 −7 M/well significantly stimulated (P<0.001) the growth as well as metabolic activity in the culture system. Interestingly, RU 486 at 10 −6 M/well did not stimulate metabolic activity in the culture. Progesterone, in combination with RU 486 at 10 −7 M/well, caused a significant increase in proliferation (assessed by thymidine incorporation) (P<0.001) over control and P 4 alone, but not significantly different from RU 486 at 10 −7 M/well alone. The same pattern was observed for metabolic functions (assessed by uridine incorporation) when RU 486 at 10 −7 M/well, along with P 4, was added to the culture. Interestingly, RU 486 at 10 −6 M/well with P 4 had no effect on RNA synthesis in the culture. The relevance of these findings is discussed.